Optimisation of calcium silicate and sand cement bricks in masonary bearing walls / Kartini Kamaruddin and Siti Hawa Hamzah - Kamaruddin, Kartini; Hamzah, Siti Hawa (Institute of Research, Development and Commercialisation (IRDC), 2006)
Design and construction of buildings used to be on framed structure incorporating reinforced concrete, steel or timber as structural member to transmit load to the foundation. Bricks are normally used as infill materials in these framed structures. However, research has shown that bricks can also be used as external and internal masonry bearing walls. With the use of structural masonry construction method, cheaper and faster construction can be achieved. Savings are obtained by using less formwork and reinforcing steel, reducing construction time as lesser frames or none are used, and eliminating waiting time for the structural concrete to cure or gain their strength. Calcium silicate and sand cement bricks were tested for their mechanical properties. Investigations were carried out on six masonry bearing walls. Each unit measured 1000 mm × 1000 mm and a half brick thick. The structural behaviour due to compressive axial load was investigated and it shows that both bricks satisfy the requirement as load bearing wall. However, the study concluded that sand cement brick wall showed better performance, with maximum lateral displacement of 3.81mm, vertical deflection of 6.63 mm and ultimate load of 448.13 kN.